Antibacterial ceramic glaze and preparation method thereof
By introducing rare earth ions and other specific components into the ceramic glaze, the shortcomings of existing antibacterial ceramic glazes in terms of antibacterial effects, gloss and flatness are solved, and higher glaze hardness, antibacterial properties and chemical corrosion resistance are achieved.
Patent Information
- Application Number
- CN202510362923.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-03-26
AI Technical Summary
The existing antibacterial ceramic glazes have shortcomings in antibacterial effects, gloss and smoothness, and are difficult to meet the needs of high hygiene standards.
An antibacterial ceramic glaze is used, and its composition includes basic glaze, nanotitanium dioxide, cosolvents, ochre, curcumin, rare earth antibacterial agent, sodium polyacrylate and composite additives. Through specific preparation and treatment methods, the rare earth ions are uniformly dispersed, stable chemical bonds are formed, and the hardness and antibacterial properties of the glaze surface are enhanced.
It significantly improves the antibacterial properties, gloss and flatness of ceramic products, enhances the hardness and chemical corrosion resistance of the glaze surface, and improves the overall performance of the product.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic glazes, in particular to an antibacterial ceramic glaze and a preparation method thereof. Background Art
[0002] Ceramic glaze is a colorless or colored glassy thin layer covering the surface of ceramic products. It is made of mineral raw materials and chemical raw materials in a certain proportion, finely ground into glaze slurry, coated on the ceramic body and calcined. The glaze layer can make the product impermeable, smooth, and not easy to stain, and to a certain extent improve the mechanical strength, electrical properties and chemical stability of the product. Colored glaze also has the function of beauty and decoration.
[0003] With the continuous development of society and the gradual improvement of living standards, people have higher and higher requirements for the quality of life, and the concept of hygienic antibacterial health care has also been deeply rooted in the hearts of the people. In order to meet people's standards in hygiene, antibacterial ceramics have emerged and have developed rapidly. Antibacterial ceramics refer to a type of ceramic products that add disinfection, sterilization and chemical degradation functions while maintaining the original use functions and decorative effects of ceramic products. These antibacterial ceramic products are widely used in industries such as hygiene, medical care, family rooms, civil or industrial buildings. In addition to adding relevant antibacterial ingredients to ceramic blanks, applying certain antibacterial ingredients to ceramic glazes is also an optional solution. However, after the introduction of antibacterial ingredients, there are also some problems that need to be solved, such as poor antibacterial effects of some antibacterial ceramics, poor glaze gloss, poor glaze flatness and smoothness, etc. Therefore, it is necessary to explore a ceramic glaze with good comprehensive effects. Summary of the invention
[0004] The purpose of the present invention is to provide an antibacterial ceramic glaze and a preparation method thereof, so as to improve the antibacterial property, glossiness and flatness of the glaze surface.
[0005] To achieve the above-mentioned purpose, the present invention provides an antibacterial ceramic glaze, comprising the following components in parts by mass: 60-75 parts of basic glaze, 1-3 parts of nano titanium dioxide, 2-6 parts of cosolvent, 0.5-3 parts of ochre, 5-10 parts of curcumin, 1-3 parts of stabilizer, 1-5 parts of rare earth antibacterial agent, 1-3 parts of sodium polyacrylate, and 1-6 parts of composite additives.
[0006] Preferably, the basic glaze comprises albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0007] Preferably, the co-solvent is at least one of zirconium silicate, sodium carbonate and borax.
[0008] Preferably, the stabilizer is at least one of calcium silicate, calcium phosphate and zirconium phosphate.
[0009] Preferably, the rare earth antibacterial agent is at least one of lanthanum chloride and cerium chloride.
[0010] Preferably, the rare earth antibacterial agent is lanthanum chloride and cerium chloride, and the mass ratio of lanthanum chloride to cerium chloride is 1:1.
[0011] Preferably, the composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is (2-4):(2-4):(1-3).
[0012] The present invention also provides a method for preparing an antibacterial ceramic glaze, comprising the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly adding a sodium hydroxide solution to the mixed solution under stirring, controlling the pH value of the solution to 9-10 and the reaction temperature to 60-80°C, filtering, washing, and drying, and then calcining at 500-700°C for 2-3h to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 2-4 hours to obtain a preliminary mixed slurry; S4, mixing the calcined product of step S2 with deionized water to prepare a solution, slowly dropping the prepared mixed solution into the preliminary mixed slurry under stirring in step S3, and continuing stirring for 1-2 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a sealed container, aging for 12-24 hours, adding ochre, curcumin, sodium polyacrylate, and composite additives, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze.
[0013] Preferably, in step S4, the calcined product is mixed with deionized water to form a solution with a mass concentration of 10-20%.
[0014] The advantages and beneficial effects of the antibacterial ceramic glaze and the preparation method thereof are as follows: 1. The introduction of rare earth ions in the present invention can refine the crystal structure of the glaze, enhance the hardness of the glaze surface, and effectively improve the wear resistance of ceramic products.
[0015] 2. The addition of rare earth chlorides in the present invention improves the melting characteristics and surface smoothness of the glaze, significantly enhances the glossiness of the ceramic glaze, and makes the product appearance more beautiful and bright. The special chemical properties of rare earth elements form stable chemical bonds in the glaze, enhance the glaze's resistance to chemical substances such as acids and alkalis, and improve the chemical corrosion resistance of the ceramic glaze.
[0016] 3. The present invention improves the antibacterial property of the glaze, protects the glaze from oxidation damage, improves the glossiness of the glaze surface formed by the glaze, affects the safety and durability of the ceramic glaze, and sodium polyacrylate and composite additives make the glaze less likely to delaminate, thereby improving the stability, uniformity and fluidity of the glaze.
[0017] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION
[0018] The technical solution of the present invention is further illustrated by the following embodiments.
[0019] Unless otherwise defined, technical or scientific terms used in the present invention shall have the common meanings understood by one having ordinary skills in the field to which the present invention belongs.
[0020] Unless otherwise defined, the reagents and equipment used in the present invention are all commercially available. Example 1
[0021] An antibacterial ceramic glaze comprises the following components in parts by mass: 60 parts of basic glaze, 1.5 parts of nano titanium dioxide, 2 parts of cosolvent, 1 part of ochre, 6 parts of curcumin, 1.5 parts of stabilizer, 2 parts of rare earth antibacterial agent, 1 part of sodium polyacrylate and 2 parts of composite additive.
[0022] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0023] The cosolvent is zirconium silicate.
[0024] The stabilizer is calcium silicate.
[0025] The rare earth antibacterial agent is lanthanum chloride.
[0026] The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is 2:2:1.
[0027] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly dropping a sodium hydroxide solution into the mixed solution under stirring conditions, controlling the pH value of the solution to 9 and the reaction temperature to 60° C., filtering, washing, and drying, and then calcining at 500° C. for 2 hours to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 4 hours to obtain a preliminary mixed slurry; S4, the calcined product of step S2 is mixed with deionized water to prepare a solution with a mass concentration of 10%, and the prepared mixed solution is slowly added dropwise to the preliminary mixed slurry under stirring in step S3, and stirring is continued for 1.5 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a closed container, aging for 18 hours, adding ochre, curcumin, sodium polyacrylate, and composite additives, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze. Example 2
[0028] An antibacterial ceramic glaze comprises the following components in parts by mass: 68 parts of basic glaze, 3 parts of nano titanium dioxide, 4 parts of cosolvent, 1.5 parts of ochre, 5 parts of curcumin, 1 part of stabilizer, 3 parts of rare earth antibacterial agent, 2 parts of sodium polyacrylate and 4 parts of composite additive.
[0029] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0030] The cosolvent is sodium carbonate.
[0031] The stabilizer is zirconium phosphate.
[0032] The rare earth antibacterial agent is cerium chloride.
[0033] The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is 3:2:2.
[0034] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly dropping a sodium hydroxide solution into the mixed solution under stirring conditions, controlling the pH value of the solution to 9.5 and the reaction temperature to 70°C, filtering, washing, and drying, and then calcining at 600°C for 2h to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 2 hours to obtain a preliminary mixed slurry; S4, mixing the calcined product of step S2 with deionized water to prepare a solution with a mass concentration of 15%, slowly dropping the prepared mixed solution into the preliminary mixed slurry under stirring in step S3, and continuing stirring for 1 hour to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a closed container, aging for 15 hours, adding ochre, curcumin, sodium polyacrylate, and composite additives, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze. Example 3
[0035] An antibacterial ceramic glaze comprises the following components in parts by mass: 75 parts of basic glaze, 1 part of nano titanium dioxide, 2 parts of cosolvent, 2 parts of ochre, 8 parts of curcumin, 2 parts of stabilizer, 4 parts of rare earth antibacterial agent, 3 parts of sodium polyacrylate and 6 parts of composite additive.
[0036] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0037] The co-solvents are sodium carbonate and borax.
[0038] The stabilizers are calcium silicate and calcium phosphate.
[0039] The rare earth antibacterial agents are lanthanum chloride and cerium chloride, and the mass ratio of lanthanum chloride to cerium chloride is 1:1.
[0040] The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is 2.5:2:1.
[0041] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly dropping a sodium hydroxide solution into the mixed solution under stirring conditions, controlling the pH value of the solution to be 10 and the reaction temperature to be 80°C, filtering, washing, and drying, and then calcining at 700°C for 3h to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 3 hours to obtain a preliminary mixed slurry; S4, mixing the calcined product of step S2 with deionized water to prepare a solution with a mass concentration of 20%, slowly dropping the prepared mixed solution into the preliminary mixed slurry under stirring in step S3, and continuing stirring for 2 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a sealed container, aging for 24 hours, adding ochre, curcumin, sodium polyacrylate, and composite additives, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze.
[0042] Comparative Example 1 An antibacterial ceramic glaze comprises the following components in parts by mass: 60 parts of basic glaze, 1.5 parts of nano titanium dioxide, 2 parts of cosolvent, 1.5 parts of stabilizer, 2 parts of rare earth antibacterial agent, 1 part of sodium polyacrylate and 2 parts of composite additive.
[0043] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0044] The cosolvent is zirconium silicate.
[0045] The stabilizer is calcium silicate.
[0046] The rare earth antibacterial agent is lanthanum chloride.
[0047] The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is 2:2:1.
[0048] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly dropping a sodium hydroxide solution into the mixed solution under stirring conditions, controlling the pH value of the solution to 9 and the reaction temperature to 60° C., filtering, washing, and drying, and then calcining at 500° C. for 2 hours to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 4 hours to obtain a preliminary mixed slurry; S4, the calcined product of step S2 is mixed with deionized water to prepare a solution with a mass concentration of 10%, and the prepared mixed solution is slowly added dropwise to the preliminary mixed slurry under stirring in step S3, and stirring is continued for 1.5 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5. The uniformly mixed slurry of step S4 is transferred to a sealed container, aged for 18 hours, and then sodium polyacrylate and composite additives are added, stirred and mixed uniformly to obtain a rare earth antibacterial ceramic glaze.
[0049] Comparative Example 2 An antibacterial ceramic glaze comprises the following components in parts by mass: 60 parts of basic glaze, 1.5 parts of nano titanium dioxide, 2 parts of cosolvent, 1.5 parts of stabilizer, 1 part of sodium polyacrylate and 2 parts of composite additive.
[0050] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0051] The cosolvent is zirconium silicate.
[0052] The stabilizer is calcium silicate.
[0053] The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is 2:2:1.
[0054] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 4 hours to obtain a preliminary mixed slurry; S3, transferring the uniformly mixed slurry of step S2 into a sealed container, aging for 18 hours, adding sodium polyacrylate and composite additives, stirring and mixing uniformly, and obtaining rare earth antibacterial ceramic glaze.
[0055] Comparative Example 3 An antibacterial ceramic glaze comprises the following components in parts by mass: 60 parts of basic glaze, 1.5 parts of nano titanium dioxide, 2 parts of cosolvent, 1 part of ochre, 6 parts of curcumin, 1.5 parts of stabilizer and 2 parts of rare earth antibacterial agent.
[0056] The basic glaze includes albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:1.
[0057] The cosolvent is zirconium silicate.
[0058] The stabilizer is calcium silicate.
[0059] The rare earth antibacterial agent is lanthanum chloride.
[0060] A method for preparing an antibacterial ceramic glaze comprises the following steps: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly dropping a sodium hydroxide solution into the mixed solution under stirring conditions, controlling the pH value of the solution to 9 and the reaction temperature to 60° C., filtering, washing, and drying, and then calcining at 500° C. for 2 hours to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 4 hours to obtain a preliminary mixed slurry; S4, the calcined product of step S2 is mixed with deionized water to prepare a solution with a mass concentration of 10%, and the prepared mixed solution is slowly added dropwise to the preliminary mixed slurry under stirring in step S3, and stirring is continued for 1.5 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a sealed container, aging for 18 hours, adding ochre and curcumin, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze.
[0061] The rare earth antibacterial ceramic glazes prepared in Examples 1-3 and Comparative Examples 1-3 were coated on ceramic green bodies, and various properties of the glazed layers formed after firing were tested. The test results are shown in Table 1.
[0062] ; As can be seen from Table 1, the rare earth antibacterial ceramic glaze of the present invention has an easy-to-clean performance of less than 0.45 g / cm 2 The antibacterial rates against Staphylococcus aureus and Escherichia coli are as high as 99.99%, the Vickers hardness is much higher than that of the comparative example, and the glossiness is good. The easy-to-clean performance, antibacterial rates against Staphylococcus aureus and Escherichia coli, Vickers hardness, and glossiness of the rare earth antibacterial ceramic glazes prepared in Comparative Example 1, Comparative Example 2, and Comparative Example 3 are not as ideal as those in Examples 1-3.
[0063] Therefore, the present invention adopts the above-mentioned antibacterial ceramic glaze and its preparation method to improve the antibacterial performance, glossiness and smoothness of the glaze. The introduction of rare earth ions can refine the crystal structure of the glaze, enhance the hardness of the glaze, and effectively improve the wear resistance of ceramic products. The special chemical properties of rare earth elements form stable chemical bonds in the glaze, enhance the glaze's resistance to acid, alkali and other chemical substances, and improve the chemical corrosion resistance of the ceramic glaze.
[0064] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.
Claims
1. An antibacterial ceramic glaze, characterized in that: The invention comprises the following components in parts by mass: 60-75 parts of basic glaze, 1-3 parts of nano titanium dioxide, 2-6 parts of auxiliary solvent, 0.5-3 parts of ochre, 5-10 parts of curcumin, 1-3 parts of stabilizer, 1-5 parts of rare earth antibacterial agent, 1-3 parts of sodium polyacrylate and 1-6 parts of composite additive.
2. The antibacterial ceramic glaze according to claim 1, characterized in that: The basic glaze comprises albite, limestone, kaolin and zinc oxide, and the mass ratio of albite, limestone, kaolin and zinc oxide is 5:3:2:
1.
3. The antibacterial ceramic glaze according to claim 1, characterized in that: The co-solvent is at least one of zirconium silicate, sodium carbonate and borax.
4. The antibacterial ceramic glaze according to claim 1, characterized in that: The stabilizer is at least one of calcium silicate, calcium phosphate and zirconium phosphate.
5. The antibacterial ceramic glaze according to claim 1, characterized in that: The rare earth antibacterial agent is at least one of lanthanum chloride and cerium chloride.
6. The antibacterial ceramic glaze according to claim 5, characterized in that: The rare earth antibacterial agent is lanthanum chloride and cerium chloride, and the mass ratio of lanthanum chloride to cerium chloride is 1:
1.
7. The antibacterial ceramic glaze according to claim 1, characterized in that: The composite additive comprises sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid, and the mass ratio of the sodium butylbenzene sulfonate, carboxymethyl chitosan and oxidized hyaluronic acid is (2-4): (2-4): (1-3).
8. The method for preparing an antibacterial ceramic glaze according to any one of claims 1 to 7, characterized in that: The steps include: S1. Crush and grind the components in the basic glaze separately, and pass them through a 200-mesh sieve to obtain powder with uniform particle size; S2, dissolving the rare earth antibacterial agent in an aqueous solution of aluminum nitrate to prepare a mixed solution, slowly adding a sodium hydroxide solution to the mixed solution under stirring, controlling the pH value of the solution to 9-10 and the reaction temperature to 60-80°C, filtering, washing, and drying, and then calcining at 500-700°C for 2-3h to obtain a calcined product; S3, adding the basic glaze treated in step S1, nano titanium dioxide, co-solvent, and stabilizer into a ball mill, adding deionized water and ball milling for 2-4 hours to obtain a preliminary mixed slurry; S4, mixing the calcined product of step S2 with deionized water to prepare a solution, slowly dropping the prepared mixed solution into the preliminary mixed slurry under stirring in step S3, and continuing stirring for 1-2 hours to ensure that the rare earth ions are evenly dispersed in the slurry; S5, transferring the uniformly mixed slurry of step S4 into a sealed container, aging for 12-24 hours, adding ochre, curcumin, sodium polyacrylate, and composite additives, stirring and mixing uniformly, and obtaining a rare earth antibacterial ceramic glaze.
9. The method for preparing an antibacterial ceramic glaze according to claim 8, characterized in that: In step S4, the calcined product is mixed with deionized water to form a solution with a mass concentration of 10-20%.
Citation Information
Patent Citations
Applique antibacterial ceramic cutter
CN101648824A
Medical composite chitosan gel containing antibacterial drug
CN106039394A
Rare earth antibacterial ceramic glaze and preparation method thereof
CN110040960A
Preparation process of organic fiber additive for concrete
CN116813238A
Wear-resistant ceramic glaze and preparation method thereof
CN118206286A
Cited By
Ceramic glaze with thermal stability and preparation method thereof
CN120423777A
Ceramic glaze with thermal stability and preparation method thereof
CN120423777B
Rare earth antibacterial ceramic and preparation method thereof
CN120441296A
A rare earth antibacterial ceramic and its preparation method
CN120441296B
Easy-to-clean glaze for ceramic products and preparation method of easy-to-clean glaze
CN120923146A